Association between 25(OH) vitamin D and graft survival in renal transplanted children. (26th August 2020) - Mosca, Mélodie; Lion‐Lambert, Mathilde; Bienaimé, Frank; Berthaud, Romain; Dorval, Guillaume; Garcelon, Nicolas; Dehoux, Laurène; Krid, Saoussen; Charbit, Marina; Rabant, Marion; Niaudet, Patrick; Salomon, Rémi; et al.
Abstract: Background: In children, vitamin D deficiency is common after renal transplantation. Besides promoting bone and muscle development, vitamin D has immunomodulatory effects, which could protect kidney allografts. The purpose of this study was to assess the association between vitamin D status and the occurrence of renal rejection. Methods: We studied a retrospective cohort of 123 children, who were transplanted at a single institution between September 2008 and April 2019. Patients did not receive vitamin D supplementation systematically. In addition, factors influencing vitamin D status were analyzed using univariate and multivariate analyses. Results: Median 25‐hydroxy‐vitamin D (25‐OH‐D) concentration was close to reference values at the time of transplantation (30 ng/mL (min‐max 5‐100)), but rapidly decreased within the first 3 months to 19 ng/mL (min‐max 3‐91) ( P < .001). The overall acute rejection rate was 7%. The clinical rejection rate (5% vs 9%), subclinical rejection (12% vs 36%), and borderline changes (21% vs 28%) were not statistically different during the follow‐up between the 3‐month 25‐OH‐D < 20 ng/mL and 3‐month 25‐OH‐D > 20 ng/mL groups. There was a correlation between the 25‐OH‐D levels and PTH concentration at 3 months ( r = −.2491, P = .01), but no correlation between the 3‐month 25‐OH‐D and the season of the year (F = 0.19, P = .90; F = 1.34, P = .27, respectively). Multivariate analyses revealed that age and mGFR at 3 months, were independent predictors of mGFR at 12 months. Conclusion: Our data show that vitamin D deficiency can develop rapidly after transplantation; vitamin D levels at 3 months are not associated with lower mGFR or a higher rejection rate at 1 year in children as opposed to adult recipients.